Intervensi Swasta dalam Pemberdayaan Masyarakat Nelayan di Desa Madapolo Kabupaten Halmahera Selatan: Studi pada Desa Madapolo Kabupaten Halmahera Selatan - Bakri La Suhu; Marno Wance; Pasid Pora; Abdulah Kaunar (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2019)
To reach an empowered and progressivefishing communities requires the participations of relevant agencies. The agencies participations are needed in empowering the fishing communities in order for them to be able to survive in the era of globalization. Taking an example, empowerment of fishing communities by the private sector in Madapolo village is perceived to be very helpful for the fishing community because after getting some assistance from the Department of Marine and Fisheries in 2000, there is no more guidance for empowerment activities given to the communities involved in this program. This studyaims atfinding outthe private intervention in empowering fishing communities in Madapolo Village. This study employsa qualitative descriptive research. The techniquesused for collecting data are direct observation techniques, interviews and documents analysis using data reduction analysis techniques, displaying data (data presentation) and verification (gathering conclusions). The primary data sources in this study includethe head of the village, the chairperson of BPD, three entrepreneurs, and nine fishermen.Meanwhile secondary data include other documents containing the pictures of empowerment results. Based on the results of the study, it reveals that the empowerment of fishing communities in Madapolo village by private agencieshasincreased several aspects in the life of fishing communities such as family income, family economic conditions and children's education. It is also found thatthe problems or barriers faced by the empowerment programsare bad weather, health problems, and family events. From the results of study, it can be concluded that the empowerment provided by the private sector is very important to increasethe fishermen's welfare in the midst of minimum assistance from the local government. Therefore, it is expected that the provided assistance can be used as well as possible.